The Effect Of Digital Marketing And Relationship Marketing On Purchasing Decisions With Purchase Intention As A Mediating Variable - Anggra Novriza; Yenni Maya Dora (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The rapid advancement of information technology in today’s digital era compels businesses to adapt swiftly to remain competitive in the marketplace. One of the most significantly affected aspects of this transformation is marketing, which is progressively shifting from traditional methods to digital platforms. Digital marketing has emerged as a core strategy for building consumer relationships and influencing purchasing decisions. This study aims to examine the influence of digital marketing and relationship marketing on consumer purchase decisions of Amanda Brownies, with purchase intention serving as a mediating variable. A quantitative approach was employed, utilizing primary data collected through questionnaires distributed to 100 Amanda Brownies consumers who had engaged with the brand via digital platforms. The findings reveal that digital marketing directly influences purchase intention by 34.3% and customer satisfaction by 32.3%. Relationship marketing has a stronger direct impact, influencing purchase intention by 60.7% and customer satisfaction by 21.7%. Furthermore, purchase intention directly contributes 43% to customer satisfaction. In terms of indirect effects, digital marketing influences purchase decisions by 14.8% through purchase intention, while relationship marketing has an indirect effect of 26.1% via the same mediating variable. These results provide valuable insights for business practitioners in designing more effective marketing strategies aimed at increasing consumer interest and converting that interest into purchasing decisions through digital engagement.